POTENSI HASIL HUTAN NON KAYU KELOMPOK PALMAE BERBASIS SISTEM INFORMASI GEOGRAFIS (SIG) DI KECAMATAN LUMBAN JULU KPHL MODEL UNIT XIV TOBASA - Tarida Olivia A Hutapea; Rahmawaty Rahmawaty; Irawati Azhar (Peronema Forestry Science Journal, 2016)
As a family of Arecaceae generally Palmae is in the form of palm or shrubs. The purpose of this study was to identify and map the distribution of Non Wood Forest Production (NWFP) group palmae along with its standing in the utilization of the potential of NWFP by the community. Field data colected from March to May 2015. The method used is systematic sampling with ramdom start with 0.5% of sampling intensity. Mapping the distribution of use software ArcView GIS 3.3. Exploration results and the identification of palmae species from 19 ha of sample plots or 475 plots contained 707 palmae rod consisting of 2 sub-families and 7 species. The results showed that the most dominant species spreading is Hotang buar-buar (Calamus scipionum Loureiro) at an altitude of 1300 m above sea level and Bagot (Arenga pinnata) at 1400 m above sea level with IVI = 71,78%; and IVI = 113,75 %. The highest species diversity index value at an altitude of 1300 m above sea level 1,64. Keyword: KPHL Tobasa, HHNK, Palmae, GIS, Lumban Julu Sub Ditrict